Design and evaluation of educational innovation laboratories as incubation spaces for teaching entrepreneurship in digital contexts - Valero-Palomino, Fiorella Rocío; Bullón-Solís, Omar; Méndez-Gutíerrez, Leidy Lucía; Bullón-Solís, Nadia; Quispe-Medina, Wilber (LACCEI, 2025)
This article presents a model of a digital teaching innovation laboratory (LIDD) with a proposal oriented towards the development of pedagogical entrepreneurship in higher education. The research, from a qualitative approach and a multiple case study in three Latin American universities, was carried out based on the finding of key factors, such as institutional articulation, organizational capacities, access to pedagogical and technological resources. The findings of the research are correlated with the four axes of a model: training, co-creation, evaluation and scaling, whose LIDD is understood as a flexible and replicable strategy that contributes to strengthening the innovative teaching culture and at the same time, collaborating for the educational transformation of university teaching-learning environments.